2013
DOI: 10.3347/kjp.2013.51.3.375
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dirofilaria immitis in Dogs in Shenyang, Northeastern China

Abstract: In the present study, we first report the seroprevalence of Dirofilaria immitis in dogs in Shenyang, northeastern China. Sera from 528 randomly selected dogs were examined for D. immitis antigen using SNAP®4Dx test kit; 12.7% tested showed seropositive. No significant difference of infection was observed in different genders and breeds (P>0.05), but the difference was significant in different age groups and rearing conditions (P<0.05). The result suggested that the risk of exposure to D. immitis in dogs is hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
7
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 13 publications
5
7
0
1
Order By: Relevance
“…As shown in Table 2 , the overall recorded seroprevalence of D. immitis in dogs in Henan province, central China was 13.18% (155/1176). Compared with other provinces or cities in China, it was lower than the values of 51.6% in dogs in a study performed in Changchun [ 8 ], 38.9% in Taiwan [ 22 ], 24.0% in Dandong [ 9 ], and 18.8% in Shenzhen [ 20 ], similar to those observed in Shenyang (12.7%) [ 13 ] and Nanning (13.3%) [ 20 ], but higher than those observed in Heilongjiang (1.1%) [ 21 ], Guizhou (5.0%) [ 7 ], Kunming (6.7%), Chongqing (10.0%), Nanchang (10.0%), and Fuzhou (12.0%) [ 20 ]. The differences in prevalence of D. immitis among these regions may be due to differences in ecological and geographical factors, detection methods used, survey periods, sample sizes, and breed of dog populations in these areas.…”
Section: Resultssupporting
confidence: 49%
See 1 more Smart Citation
“…As shown in Table 2 , the overall recorded seroprevalence of D. immitis in dogs in Henan province, central China was 13.18% (155/1176). Compared with other provinces or cities in China, it was lower than the values of 51.6% in dogs in a study performed in Changchun [ 8 ], 38.9% in Taiwan [ 22 ], 24.0% in Dandong [ 9 ], and 18.8% in Shenzhen [ 20 ], similar to those observed in Shenyang (12.7%) [ 13 ] and Nanning (13.3%) [ 20 ], but higher than those observed in Heilongjiang (1.1%) [ 21 ], Guizhou (5.0%) [ 7 ], Kunming (6.7%), Chongqing (10.0%), Nanchang (10.0%), and Fuzhou (12.0%) [ 20 ]. The differences in prevalence of D. immitis among these regions may be due to differences in ecological and geographical factors, detection methods used, survey periods, sample sizes, and breed of dog populations in these areas.…”
Section: Resultssupporting
confidence: 49%
“…There are many reports on the prevalence of D. immitis infection in dogs from various countries, including Korea [ 3 ], Iran [ 10 ], Poland [ 11 ], Portugal [ 1 ], Costa Rica [ 18 ], and Hungary [ 2 ]. In recent years, studies of D. immitis infection in dogs have been undertaken in different regions of China ( Table 1 [ 6 9 , 13 , 20 22 ]). These reports show that canine dirofilariasis is endemic in China.…”
Section: Introductionmentioning
confidence: 99%
“…There is very little reliable information on vector-borne agents in dogs in China with only eight reports for the entire country: three using serology (7, 10, 11), one using PCR (13), three using serology and PCR (9, 14, 15), and one using PCR and microscopy (12). Studies with PCR and/or serology methods have indicated the E. canis occurs in dogs from Shenzhen, Guangzhou and Hong Kong [ 7 9 ] and D. immitis in dogs from Beijing, Shanghai, Chongqing, Yunnan, Guangdong and Shenyang provinces/ municipalities [ 7 , 10 , 11 ]. Molecular based studies have shown D. immitis in dogs from Liaoning province [ 12 ] and leishmaniasis to be common in dogs in Sichuan province [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…D. immitis has been frequently detected in cats in many countries, including the United States [ 7 ], Canary Islands [ 8 ], Malaysia [ 9 ], Korea [ 10 ], Portugal [ 11 ], and Italy [ 12 ]. In China, several studies have reported the prevalence of D. immitis in dogs, 12.7% in Shenyang city and 24.0% in Dandong city, northeastern China [ 13 , 14 ], 13% in Henan province and 31.2% in Xian city, central China [ 15 , 16 ]. The prevalence is 13.5% in southern China, such as Nanchang, Fuzhou, Guangzhou, Shenzhen, Nanning [ 17 ].…”
mentioning
confidence: 99%